2009
DOI: 10.1002/adfm.200800954
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Photovoltaic Cells Based on Solution‐Processable Graphene and P3HT

Abstract: A soluble graphene, which has a one‐atom thickness and a two‐dimensional structure, is blended with poly(3‐hexylthiophene) (P3HT) and used as the active layer in bulk heterojunction (BHJ) polymer photovoltaic cells. Adding graphene to the P3HT induces a great quenching of the photoluminescence of the P3HT, indicating a strong electron/energy transfer from the P3HT to the graphene. In the photovoltaic devices with an ITO/PEDOT:PSS/P3HT:graphene/LiF/Al structure, the device efficiency increases first and then de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
310
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(322 citation statements)
references
References 93 publications
9
310
1
2
Order By: Relevance
“…An OPV based on the hybrid of graphene and poly(3-hexylthiophene) (P3HT) was also fabricated and annealed. 108 It exhibited a PCE of 1.1%, open circuit voltage of 0.72 V, a short circuit current density of 4.0 mA cm À2 , and a FF of 0.38 upon excitation with AM 1.5 simulated sunlight at 100 mW cm À2 . The efficiencies are still far from those of the state-of-the-art OPVs, possibly because of the irregular molecular structure of rGO; however, graphene-based cells exhibited higher efficiencies than most of the best OPVs based on other alternative acceptor materials to C60 derivatives.…”
Section: Heterojunction Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…An OPV based on the hybrid of graphene and poly(3-hexylthiophene) (P3HT) was also fabricated and annealed. 108 It exhibited a PCE of 1.1%, open circuit voltage of 0.72 V, a short circuit current density of 4.0 mA cm À2 , and a FF of 0.38 upon excitation with AM 1.5 simulated sunlight at 100 mW cm À2 . The efficiencies are still far from those of the state-of-the-art OPVs, possibly because of the irregular molecular structure of rGO; however, graphene-based cells exhibited higher efficiencies than most of the best OPVs based on other alternative acceptor materials to C60 derivatives.…”
Section: Heterojunction Solar Cellsmentioning
confidence: 99%
“…As a novel and unique member of the carbon nanomaterials family, graphene is an attractive material for fabricating transparent electrodes 27,43,141 and improving the performances of dyesensitized 15,142,143 and heterojunction solar cells. [108][109][110] Transparent Conducting Electrodes TCEs are a key component of optoelectronic devices. The ideal TECs should possess high transparency (>80%), low resistance (<100 X/&), and an appropriate work function (4.5-5.2 eV).…”
Section: Solar Cellsmentioning
confidence: 99%
“…PCEs as high as 1.4% at 10 wt% FCCG in P3HT or poly-3-octylthiophene were obtained. 121,122 The importance of annealing was established definitively, with PCE improving from 0.15 to 1.1%. Remarkably, the observed open circuit voltage was higher than predicted theoretically, suggesting that the work function of FCCG differs from that of pristine graphene.…”
Section: Nanoscale Assembly T Emrick and E Pentzermentioning
confidence: 99%
“…Scanning electron microscopy characterization of the thin film showed continuous pathways for electron transport at 10 wt% GO in the active layer, and platelet orientation parallel to the underlying substrate (and thus the electrodes) prevented short circuiting. 122,123 Phenyl-functionalized GO (10 wt%) has also been blended with a P3HT/PC 60 BM composite (1:1) in attempts to bridge fullerene domains and provide continuous pathways for electron transport. After thermal annealing of devices at 160 1C, to reduce GO to FCCG and generate polymer fibrils, a PCE of 1.4% was obtained, compared with 0.88% PCE without FCCG.…”
Section: Nanoscale Assembly T Emrick and E Pentzermentioning
confidence: 99%
“…It has been reported that graphene-based materials and composites can be used as transparent electrodes [90,91] and electron acceptors in PSCs [92][93][94][95].…”
Section: Use Of Grapheme-based Materials In Clean Energy Applicationsmentioning
confidence: 99%